2021
DOI: 10.1038/s41598-021-85509-7
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic tolerance is associated with a broad and complex transcriptional response in E. coli

Abstract: Antibiotic treatment kills a large portion of a population, while a small, tolerant subpopulation survives. Tolerant bacteria disrupt antibiotic efficacy and increase the likelihood that a population gains antibiotic resistance, a growing health concern. We examined how E. coli transcriptional networks changed in response to lethal ampicillin concentrations. We are the first to apply transcriptional regulatory network (TRN) analysis to antibiotic tolerance by leveraging existing knowledge and our transcription… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 107 publications
2
30
0
Order By: Relevance
“…All the experiments in which it was not possible to uniquely identify the exact growth conditions and/or the nature of the antimicrobial compound were disregarded for downstream analyses. This search led to the identification of six studies (22, 23, 24, 25, 26, 27) accounting for seven experiments (control vs. treatment), using as antimicrobials triclosan (TCS), colistin (CST), thioacetamide-linked 1,2,3-triazole (TAT), ampicillin (AMP), ciclopirox (CPX), erythromycin (ERY) and clindamycin (CLI), as listed in Table S1. We refer to “NAM” and “WAM” models to indicate the control (no antimicrobial) and treatment (with antimicrobial) conditions, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…All the experiments in which it was not possible to uniquely identify the exact growth conditions and/or the nature of the antimicrobial compound were disregarded for downstream analyses. This search led to the identification of six studies (22, 23, 24, 25, 26, 27) accounting for seven experiments (control vs. treatment), using as antimicrobials triclosan (TCS), colistin (CST), thioacetamide-linked 1,2,3-triazole (TAT), ampicillin (AMP), ciclopirox (CPX), erythromycin (ERY) and clindamycin (CLI), as listed in Table S1. We refer to “NAM” and “WAM” models to indicate the control (no antimicrobial) and treatment (with antimicrobial) conditions, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, genes for which insertions were more negatively selected compared to PEN appeared to be involved in general stress responses rather than compound uptake. These included transcriptional regulators such as rpoS , which encodes the central regulator of the general stress response in E. coli and which has previously been observed to play a role in AMP resistance ( 17 ).…”
Section: Observationmentioning
confidence: 99%
“…This is due to the mismatch between the cell's relatively low number of proteases and the high number of proteins (table 1). Proteolytic queueing has been observed in wild-type bacteria during stress conditions and linked to up-regulation of the sigma factors σ S and σ 32 [24,[174][175][176][177]. It is also associated with antibiotic survival strategies [177,178].…”
Section: Synthetic Oscillators and Degradation Bottlenecksmentioning
confidence: 99%
“…Proteolytic queueing has been observed in wild-type bacteria during stress conditions and linked to up-regulation of the sigma factors σ S and σ 32 [24,[174][175][176][177]. It is also associated with antibiotic survival strategies [177,178]. In vivo experiments showed that ClpXP often works near or in a saturated regime, and that queueing can lead to coupling between unrelated proteins targeted by the same proteolytic complex [40].…”
Section: Synthetic Oscillators and Degradation Bottlenecksmentioning
confidence: 99%